2017
DOI: 10.1111/bjh.14616
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis between RQPCR and digital droplet PCR of BCL2/IGH gene rearrangement in the peripheral blood and bone marrow of early stage follicular lymphoma

Abstract: BCL2/IGH rearrangements were analysed by polymerase chain reaction (PCR) at diagnosis in paired peripheral blood (PB) and bone marrow (BM) samples from 67 patients with stage I/II follicular lymphoma (FL). Real time quantitative PCR (RQ-PCR) and digital droplet PCR (ddPCR) were performed in cases with a major breakpoint region (MBR+) at diagnosis and after localized radiotherapy and rituximab administration in order to investigate the applicability of ddPCR. The overall ddPCR/RQ-PCR concordance was 81·9% (113/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…This is in line with previous studies showed that ddPCR and RQ exhibit a good correlation in MRD quantification in different diseases; moreover, in samples with low MRD levels, ddPCR appears able to identify a quantifiable disease more reliably than RQ and to discriminate very low MRD level from false positive samples …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is in line with previous studies showed that ddPCR and RQ exhibit a good correlation in MRD quantification in different diseases; moreover, in samples with low MRD levels, ddPCR appears able to identify a quantifiable disease more reliably than RQ and to discriminate very low MRD level from false positive samples …”
Section: Discussionsupporting
confidence: 92%
“…ddPCR appears a promising tool for MRD monitoring . Based on the dynamic nature of the method, ddPCR seems to be more accurate than RQ since (a) each sample is partitioned in thousands of droplets, representing thousands of independent PCR, and each droplet is analyzed individually; (b) small changes in fluorescence intensity are more readily detected; and (c) the ratio between target DNA molecules to PCR reagents is substantially higher .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, only a few studies, afterwards described, report dPCR use for MRD monitoring in lymphoprolipherative disorders [ 23 , 42 , 43 , 44 , 45 , 46 , 47 ]. Actually, more progresses have been achieved by dPCR for MRD evaluation in other hematological malignancies.…”
Section: Digital Pcr For Mrd Monitoringmentioning
confidence: 99%